Preoperative Stress Testing before Non-Cardiac Surgery - Olga Dzhioeva; Marijana Tadic; Evgeny Belyavskiy (Reviews in Cardiovascular Medicine, 2023)
The current guidelines from various medical societies provide a good summary of data regarding various preoperative exercise tests in patients prior to non-cardiac surgical interventions. However, there is no consensus among experts on the appropriateness of these methods for identifying risk groups for potential perioperative complications. A large volume of published studies describes the role of preoperative exercise stress testing impact in improving the prediction of potential cardiovascular (CV) risk in patients after non-cardiac surgery. Numerous stress tests are available in clinical practice, and the methods used and the best choice depends on the purpose of the study and the availability of equipment in the hospital. Traditionally, the value of exercise electrocardiography (ECG), or ECG stress test, has been based on the belief that it is beneficial for perioperative cardiac risk prediction. However, in the past two decades, the key role of this method has lost its importance due to the growing trend toward the use of imaging techniques. Moreover, in light of current trends, the six-minute walk test (6MWT) is a helpful tool in preoperative assessment and plays an important role in postoperative rehabilitation. Interestingly, the recent finding showed how 6MWT affects the risk of postoperative complications. Cardiopulmonary testing, as a dynamic clinical tool, determines the cardiorespiratory status of a patient. Various clinical indications for cardiopulmonary exercise testing include evaluation of therapy, stratification of risk factors, diagnosis of disease, and control of physical activity. Stress testing is one of the most practical ways of predicting perioperative risk and managing patients. This test is based on ischemia provoked by pharmacological agents or exercise. There is no established evidence of a significant advantage of pharmacological stress over exercise stress imaging in subjects who are capable enough to be physically active. All of these studies examined a stress test for induced myocardial ischemia. Currently, there are no data on the use of ischaemic stress tests, especially diastolic stress tests, in the assessment of perioperative risk before non-cardiac surgical interventions. We consider it promising and essential to continue research in this direction in patients with coronary heart disease and other categories of cardiac patients, in particular, comorbid and low-symptomatic individuals, before elective high-risk surgical interventions.